2013
DOI: 10.1074/jbc.m113.475657
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-7 Suppresses the Invasive Potential of Breast Cancer Cells and Sensitizes Cells to DNA Damages by Targeting Histone Methyltransferase SET8

Abstract: Background: How SET8 is regulated is not fully understood. Results: MicroRNA-7 down-regulates SET8 and inhibits H4K20 monomethylation, suppresses metastasis of breast cancer cells, and sensitizes cells to DNA damages. Conclusion: MicroRNA-7 is a negative regulator of SET8. Significance: This work aids our understanding of the biological function of microRNA-7, supporting the pursuit of microRNA-7 as a potential target for breast cancer intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 51 publications
0
36
0
2
Order By: Relevance
“…SET8 also called PR-Set7/9, KMT5A or SETD8, is one of the SET domain-containing methyltransferases that specifically targets histone H4 lysine 20 (H4K20) for monomethylation, and which exerts diverse biological processes, including activation or silencing of gene transcription (35,36), maintaining chromosome structure and stability (37,38), regulating the cell cycle and preventing premature chromatin compaction in the S phase (39,40), and rescuing and degrading DNA damage (41,42). Yu et al found that miR-7 suppressed the invasive potential of breast cancer cells by targeting SET8 (43). However, the role of SET8 in cervical cancer metastasis and how the expression of SET8 is regulated are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…SET8 also called PR-Set7/9, KMT5A or SETD8, is one of the SET domain-containing methyltransferases that specifically targets histone H4 lysine 20 (H4K20) for monomethylation, and which exerts diverse biological processes, including activation or silencing of gene transcription (35,36), maintaining chromosome structure and stability (37,38), regulating the cell cycle and preventing premature chromatin compaction in the S phase (39,40), and rescuing and degrading DNA damage (41,42). Yu et al found that miR-7 suppressed the invasive potential of breast cancer cells by targeting SET8 (43). However, the role of SET8 in cervical cancer metastasis and how the expression of SET8 is regulated are poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Setd8 and H4K20me1 are also thought to be transcriptional regulators (7,15,(17)(18)(19)(20)(21)(22)(23)(24)(25); however, in contrast to some of the better-characterized histone modifications (e.g., histone H3 lysine 4 methylation), the influence of this epigenetic pathway on gene expression has not been clearly defined. Disruption of the Setd8/H4K20me1 pathway has been associated with a number of human cancers, including leukemia (26)(27)(28)(29)(30), highlighting the relevance of this pathway to human health and disease.…”
mentioning
confidence: 99%
“…In our analysis, we observed that hsa_circ_0001946, also known as CDR1as, is differentially regulated in early stage breast tumors. Overexpression of CDR1as decoys miR-7 with its 73 binding sites causing tumor promotion through epithelialto-mesenchymal transition, invasion and metastasis [29][30][31] . Oncogenic potential of CDR1as through miR-7 sponging has been shown in gastric cancer and carcinoma of liver, esophagus and lung 19,[32][33][34] .…”
Section: Discussionmentioning
confidence: 99%